The effects of storytelling in the promotion of physical activity for chronically ill patients: an integrative review. (2nd August 2020) - Byrne, Charlotte; Soundy, Andy
Abstract : Background/Aims: Physical activity is regarded as an essential component of self-management for people with chronic illness. Storytelling is an approach that successfully uses a group environment to influence change in physical activity intentions and behaviours. The aim of this study was to develop an understanding of what a storytelling intervention entails, its main effects and how this leads to the promotion of physical activity in chronically ill patients. Methods: An integrative review was undertaken in three stages: search, appraisal and synthesis. Studies were included if they represented participants with a chronic illness, used a storytelling approach for the intervention and had physical activity as a component of the intervention. Results: A total of 14 articles were identified that included a total of 818 participants (191 male, 348 female, 279 unknown). No articles were identified as flawed and all were included in the synthesis. Four themes were identified: ideal processes within interventions; psychosocial factors that influenced storytelling; perceived outcomes relating to storytelling; and perceived benefits of physical activity. Conclusions: This review develops a deeper understanding of the required processes, associated factors and outcomes of storytelling interventions for people with chronic illness. It provides evidence of how storytelling can be used to promote physical activity. Further research into storytelling interventions is required.